Design of an arduino based Maximum Power Point Tracking (MPPT) solar charge controller - Dutta, Ananya; Barua, Niloy; Saha, Aninda (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.